PELATIHAN PEMBUATAN MEDIA PENGAJARAN INTERAKTIF BAGI GURU SLB NEGERI 3 JAKARTA - Perdana, Novario Jaya; Valencia; Jane Syahwalina Kaprica Sandra; Gilang Samudro (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2025)
Education is very important for every generation in Indonesia. Good education is one that keeps up with the development of science and technology. With the advancement of technology today, education in Indonesia should also develop, especially with the entry of the era of evolution 4.0 which relies on technology as a medium for any activity, including learning. Learning media is a tool to help the teaching and learning process between educators and students in realizing good and technology-based learning. Good learning media will support a creative, innovative and collaborative learning process. The creation of good learning media can utilize current technological developments. The use of the latest information technology requires teachers' skills to be more honed. This community service activity was carried out in collaboration with SLB Negeri 3 Jakarta to provide training in creating interactive learning media using the Canva application. This application was chosen because of its abundant features to help the process of creating learning media, besides that its use is relatively easier compared to similar applications. The activity has been successfully carried out with fifty participants, teachers from partner schools and schools in the same environment. Based on the evaluation, it was found that this training succeeded in providing additional knowledge for the participants. ABSTRAK Pendidikan merupakan hal yang sangat penting bagi setiap generasi di Indonesia. Pendidikan yang baik adalah yang tetap mengikuti perkembangan ilmu pengetahuan dan teknologi. Dengan kemajuan teknologi saat ini, seharusnya pendidikan di Indonesia juga berkembang terutama dengan telah masuknya era evolusi 4.0 yang mengandalkan teknologi sebagai media dari kegiatan apapun, tak terkecuali pembelajaran. Media pembelajaran adalah suatu alat dalam membantu proses belajar mengajar antara pendidik dengan peserta didik dalam mewujudkan pembelajaran yang baik dan berbasis teknologi. Media pembelajaran yang baik akan mendukung proses belajar yang kreatif, inovatif dan kolaboratif. Pembuatan media pembelajaran yang baik dapat memanfaatkan perkembagan teknologi saat ini. Penggunaan teknologi informasi terkini menuntut keterampilan guru agar lebih terasah. Kegiatan pengabdian ini dilaksanakan bekerja sama dengan SLB Negeri 3 Jakarta untuk memberikan pelatihan pembuatan media pembelajaran yang interaktif dengan menggunakan aplikasi Canva. Aplikasi ini dipilih karena fitur yang berlimpah untuk membantu proses pembuatan media pembelajaran, selain itu juga penggunaannya yang relatif lebih mudah dibandingkan dengan aplikasi sejenis. Kegiatan sudah berhasil dilaksanakan dengan peserta sebanyak lima puluh orang guru yang berasal dari sekolah mitra dan sekolah-sekolah di lingkungan yang sama. Berdasarkan evaluasi, didapatkan bahwa pelatihan ini berhasil memberikan pengetahuan tambahan bagi para peserta.